Perceived exertion in coaches and young swimmers with different training experience - Barroso, R.; Cardoso, R. K.; Crivoi Carmo, E.; Tricoli, V. (International Journal of Sports Physiology and Performance, 2014)
Session rating of perceived exertion (SRPE) is a practical method to assess internal training load to provide appropriate stimuli. However, coaches and athletes might rate training sessions differently, which can impair performance development. In addition, SRPE might be influenced by athletes` training experience. The authors studied 160 swimmers of different age groups and different competitive swimming experience and 9 coaches. SRPE was indicated by the swimmers 30 min after the end of a training session and before the training session by the coaches. Training-session intensities were classified into easy (SRPE <3), moderate (SRPE 3-5), and difficult (SRPE >5), based on coaches` perception. We observed that the correlation between coaches` and athletes` SRPE increased with increased age and competitive swimming experience, r = .31 for the 11- to 12-y-old group (P < .001), r = .51 for the 13- to 14-y-old group (P < .001), and r = .74 for the 15- to 16-y-old group (P < .001). In addition, younger swimmers (11-12 y, P < .01; 13-14 y, P < .01) rated training intensity differently from coaches in all 3 categories (easy, moderate, and difficult), while the older group rated differently in only 1 category (difficult, P < .01). These findings suggest that the more experienced swimmers are, the more accurate their SRPE is.